A Study on the Role of SIDBI in Promoting and Developing MSMEs in India - Devaraju, Dr; Prathap , Dr.; Kumar, Dilip (Electronic Journal of Business and Management, 2023)
This research paper explores the vital role of the Small Industries Development Bank of India (SIDBI) in advancing Micro, Small, and Medium Enterprises (MSMEs) in India. This study tracks the performance of government and SIDBI initiatives, evaluating their impact on MSME empowerment. It assesses government initiatives for MSME improvement, SIDBI’s measures for empowerment, and examines MSMEs’ influence on GDP and employment. Additionally, it analyzes SIDBI’s role in supporting MSMEs through refinancing to diverse financial entities. The study found consistent growth in financial assistance for loans, significant refinancing support from SIDBI to financial entities, particularly MFIs and NBFCs, and increased direct loans to MSMEs. This reflects SIDBI’s commitment to enhancing financial stability and promoting MSME growth. Additionally, the study highlights the crucial role of MSMEs in driving employment and GDP growth in India. The analysis relies on secondary data collected from research articles, magazines, textbooks, and annual reports of RBI, MSMEs, SIDBI, MUDRA, and PIB websites which are relevant to the topic. Recommendations include: SIDBI should streamlining procedures for smoother credit flow and prioritising direct lending to cater to diverse MSME needs. Institutions related to MSMEs should establish separate customer care departments. SIDBI should incentivize MSMEs to develop R&D facilities and focus on sustaining GDP contribution by facilitating easier access to finance. Efforts to promote all MUDRA loan categories and address loan defaults should be sustained by SIDBI.